2012
DOI: 10.26719/2012.18.8.811
|View full text |Cite
|
Sign up to set email alerts
|

Controlling medicine prices in Sudan: the challenge of the recently established Medicines Regulatory Authority

Abstract: This study evaluated the capacity of the medicine pricing mechanism of the National Medicines and Poisons Board (NMPB), the medicine regulatory agency of Sudan, in controlling prices of imported medicines. The study was conducted between July and September 2008 and data on the 50 most sold medicines in 2007 were obtained from the records of the regulatory authority and pharmacies in Khartoum; 135 products were included. The cost and freight (C&F) prices of 23% of the selected medicines approved by NMPB were ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 3 publications
0
35
0
2
Order By: Relevance
“…Weak systems for government direct price control may not lead to the required outcome. As revealed in Sudan (52) and Philippines (72), regulation of medicines prices does not guarantee reduction in the prices of essential medicines and improved availability and affordability. It is therefore important to critically examine appropriateness of implementation approaches for achieving outcomes within speci c contexts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Weak systems for government direct price control may not lead to the required outcome. As revealed in Sudan (52) and Philippines (72), regulation of medicines prices does not guarantee reduction in the prices of essential medicines and improved availability and affordability. It is therefore important to critically examine appropriateness of implementation approaches for achieving outcomes within speci c contexts.…”
Section: Discussionmentioning
confidence: 99%
“…A study in China also revealed contextual barriers such as lack of enforcement of pricing regulations and policies, with authors encouraging strong governance structures and legal frameworks to ensure enforcement (85). The monitoring and enforcement of medicines pricing frameworks need to be supported by well trained and skilled personnel, which is often lacking in different SSA countries (52,54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting with a description of regulatory policies in Norway [70], and China [71], peer-reviewed literature initially featured mainly high-income countries. More recently a number of similar peer-reviewed studies have been published on LMIC countries [72]. OECD and WHO have, in contrast, been regularly publishing similar studies on LMIC, frequently available in non-English or even the native country languages.…”
Section: Discussionmentioning
confidence: 99%